2021
DOI: 10.1001/jamanetworkopen.2021.10314
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes Among US Patients Hospitalized for Ischemic Stroke Before vs During the COVID-19 Pandemic

Abstract: IMPORTANCE After the emergence of COVID-19, studies reported a decrease in hospitalizations of patients with ischemic stroke (IS), but there are little to no data regarding hospitalizations for the remainder of 2020, including outcome data from a large cohort of patients with IS and comorbid COVID-19. OBJECTIVE To assess hospital discharge rates, demographic factors, and outcomes of hospitalization associated with the COVID-19 pandemic among US patients with IS before vs during the COVID-19 pandemic. DESIGN, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
1
20
2
Order By: Relevance
“…During the early stages of the global COVID-19 pandemic, the prevalence of hospitalization for acute ischemic stroke (AIS) decreased and, in some countries, AIS case fatality rose. [1][2][3][4][5][6][7][8][9] These findings are unusual given that the overwhelming majority of cases were SARS-CoV-2-negative patients and hospitals in most parts of the world were accessible for emergency stroke care without significant interruption of service. 1,[10][11][12] The most commonly suggested explanation is that fear of hospital-acquired COVID-19 caused AIS patients to delay or defer hospital presentation.…”
Section: Introductionmentioning
confidence: 94%
“…During the early stages of the global COVID-19 pandemic, the prevalence of hospitalization for acute ischemic stroke (AIS) decreased and, in some countries, AIS case fatality rose. [1][2][3][4][5][6][7][8][9] These findings are unusual given that the overwhelming majority of cases were SARS-CoV-2-negative patients and hospitals in most parts of the world were accessible for emergency stroke care without significant interruption of service. 1,[10][11][12] The most commonly suggested explanation is that fear of hospital-acquired COVID-19 caused AIS patients to delay or defer hospital presentation.…”
Section: Introductionmentioning
confidence: 94%
“…In this period, it is conceivable that patients were hospitalized only for severe illnesses. Furthermore, access to the hospital appeared delayed, compared with that in previous years [17].…”
Section: Discussionmentioning
confidence: 94%
“…In emergency departments (EDs), it was reported that the rate of admission for critical patients was inversely related to the rate of admission for non-critical patients [16]. A clear reduction in hospitalizations for heart diseases during the beginning of the COVID-19 pandemic was observed [17]; the reduced number of hospital admissions has resulted in an increase in out-of-hospital deaths and long-term complications [18]. In a French study, a numerical increase in the rate of in-hospital deaths during the lockdown was observed; the increase was less than that found in an Iranian set [19].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical database in the US, again driven mostly by academic centers, examined monthly discharges with the diagnosis of ischemic stroke and found decreasing numbers in March and April 2020. Numbers returned to pre‐pandemic levels by July 2020 [ 18 ]. In a multinational study involving 457 stroke centers from 70 countries, a decrease of 11.5% in the admission rate and a decrease of 13.2% in thrombolysis treatment were observed [ 19 ].…”
Section: Discussionmentioning
confidence: 99%